2018
DOI: 10.14423/smj.0000000000000821
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Analysis of Patient Age and Other Disparities in the Treatment of Ovarian Cancer in Central Appalachia and Kentucky

Abstract: When the treatment of ovarian cancer did not follow NCCN recommendations, patients had a significantly higher risk of death. Women were less likely to receive NCCN-compliant care if they were younger (20-49 years), had early-stage disease, did not have private insurance, or had care provided at a nontertiary care hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…3,[9][10][11][12][13] Despite the evidence of improved outcomes and NCCN recommendations, as many as 30% of women with ovarian cancer in the United States and nearly 15% of women in Iowa are not receiving surgical care from a gynecologic oncologist. 11,[14][15][16][17][18][19][20] Researchers have hypothesized this discrepancy between recommended and received care is due to the incidental diagnosis, discovery of cancer during non-cancer surgery and disagreement about standards of care. 21,22 Low referral rates may also be associated with receipt of care at a rural hospital or a low-volume hospital, and lower patient income or a lack of insurance.…”
Section: Introductionmentioning
confidence: 99%
“…3,[9][10][11][12][13] Despite the evidence of improved outcomes and NCCN recommendations, as many as 30% of women with ovarian cancer in the United States and nearly 15% of women in Iowa are not receiving surgical care from a gynecologic oncologist. 11,[14][15][16][17][18][19][20] Researchers have hypothesized this discrepancy between recommended and received care is due to the incidental diagnosis, discovery of cancer during non-cancer surgery and disagreement about standards of care. 21,22 Low referral rates may also be associated with receipt of care at a rural hospital or a low-volume hospital, and lower patient income or a lack of insurance.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Thiels et al and Visser et al found 30.1% of patients with gastric cancer and 34.5% of patients with pancreatic cancer, respectively, received guideline-adherent care [30,31]. Rates of compliance have ranged from as low as around 30% to higher rates of compliance from nearly 60-80% compliance, depending on cancer type and region of practice [16,23,32,33]. One potential explanation for the high proportion of NCCN AdC observed in our study compared with reports in other cancers is that, in general, there is greater consensus on the guidelines for the treatment of ASCC, supported by clinical trial-based research.…”
Section: Discussionmentioning
confidence: 97%